2004
DOI: 10.5194/npg-11-383-2004
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow disaggregation: a nonlinear deterministic approach

Abstract: Abstract. This study introduces a nonlinear deterministic approach for streamflow disaggregation. According to this approach, the streamflow transformation process from one scale to another is treated as a nonlinear deterministic process, rather than a stochastic process as generally assumed. The approach follows two important steps: (1) reconstruction of the scalar (streamflow) series in a multidimensional phase-space for representing the transformation dynamics; and (2) use of a local approximation (nearest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Similar results on the effects of scale on hydrologic process complexity (i.e. increase in complexity or change from determinism to stochasticity with increasing time scale) were also observed by a few other studies as well (e.g., Sivakumar et al 2004Sivakumar et al , 2006Salas et al 2005;Sivakumar and Chen 2007), albeit in different contexts and employing different methodologies to different systems and processes (including rainfall, river flow and sediment load). There may indeed be exceptions to this situation with no trend possibly observed in the 'scale versus complexity' relationship [see Sivakumar et al (2001b) for details], since this relationship essentially depends on, for example, rainfall characteristics (e.g.…”
Section: Scale and Scale-invariancesupporting
confidence: 74%
“…Similar results on the effects of scale on hydrologic process complexity (i.e. increase in complexity or change from determinism to stochasticity with increasing time scale) were also observed by a few other studies as well (e.g., Sivakumar et al 2004Sivakumar et al , 2006Salas et al 2005;Sivakumar and Chen 2007), albeit in different contexts and employing different methodologies to different systems and processes (including rainfall, river flow and sediment load). There may indeed be exceptions to this situation with no trend possibly observed in the 'scale versus complexity' relationship [see Sivakumar et al (2001b) for details], since this relationship essentially depends on, for example, rainfall characteristics (e.g.…”
Section: Scale and Scale-invariancesupporting
confidence: 74%
“…This obviously necessitates understanding and/or ''transforming'' the process of interest at the scale of interest from the corresponding process at another scale (which may be either upscaling or downscaling). Extensive details of the scale issue in hydrology are already available in the literature (e.g., Gupta andWaymire 1990, 1998;Gupta et al 1994Gupta et al , 1996Blöschl and Sivapalan 1995;Gupta and Dawdy 1995;Kalma and Sivapalan 1996;Gupta 2004;Sivakumar et al 2004), and therefore are not reported herein.…”
Section: Hydrologic Systems and Current Modeling Trendmentioning
confidence: 96%
“…For instance, the phase-space diagram reflects the increasing complexity in the dynamic evolution of flow (in the Mississippi River basin) with aggregation of data in temporal scale (from daily to 16-day), a possible implication that the actual (number of) dominant processes are different at these different scales. This observation is particularly interesting, since our general intuition is that complexity of a system decreases with aggregation in temporal scale [see Sivakumar et al (2004) for further details, especially through a data disaggregation approach].…”
Section: Catchment Classification Framework: Role Of Dominant Processesmentioning
confidence: 96%
“…Such a question still remains to be answered, and will be investigated in a future study. Nevertheless, our opinion, for the moment, especially based on nonlinear dynamic studies on streamflow (and other hydrologic data) and complex network studies on rainfall at different temporal scales, is that the streamflow network properties (including degree centrality, clustering coefficient, and degree distribution) may change for other temporal scales, despite the possible presence of scaling (or fractal) behavior in streamflow; see Sivakumar (2001), Sivakumar et al (2001Sivakumar et al ( , 2004Sivakumar et al ( , 2007, Regonda et al (2004), Salas et al (2005), Jha and Sivakumar (2017), and Naufan et al (2017) for some details. We hope to provide more reliable and convincing answers to this question in a future study, as we are currently conducting additional research on network properties in terms of scale and network size.…”
Section: Discussion Of Resultsmentioning
confidence: 99%